Bioactivity of the essential oil extracted from Evodia rutaecarpa Hook f. et Thomas against the grain storage insects, Sitophilus zeamais Motsch. and Tribolium castaneum (Herbst) - Liu, Z.L. (2014)
10.1016/S0022-474X(99)00015-6